Colt Group S.A. announces global expansion of the Information Delivery Platform through proposed acquisition of KVH (M2 Presswire, 2014)
- Colt and KVH operate complementary businesses with similar technology and platforms, business models and product sets. KVH's business is well known to Colt's key management, which is expected to assist with implementing Colt's integration plans - KVH is owned 100% by FMR, FIL and associates of FMR, and FIL. FMR, FIL and certain of their associates are also shareholders of Colt. The Transaction constitutes a related party transaction which is subject to the approval of Independent Shareholders. Accordingly, a General Meeting will be held at 10.00 a.m. (Luxembourg time) on 16 December 2014 at K2 Building, Forte 1, 2a rue Albert Borschette, L-1246, Luxembourg at which the approval of the Company's shareholders will be sought for the Transaction "We are delighted to formally become part of the Colt family. The combination of our two companies will add scale, improve the competitiveness of both KVH and Colt, and be beneficial to all our customers. KVH will provide an established and successful platform - deploying its assets, relationships and people - for growth in Asia as part of a larger Colt organisation. We look forward to being able to leverage Colt's operating experience, customer relationships, technology platform, and advanced processes, systems and best practices."